Prevalence of lower urinary tract symptoms related to benign prostatic hyperplasia in a urology outpatient clinic in the state of Maranhão (Revista Brasileira Multidisciplinar, 2023)
Abstract: Benign prostatic hyperplasia (BPH) is a pathophysiological process responsible for most lower urinary tract symptoms (LUTS). The prevalence of BPH remains difficult to determine, especially due to the non-standardization of criteria in the characterization of this clinical condition. This study aimed to analyze the clinical and epidemiological characteristics of individuals with LUTS associated with BPH at a urology outpatient clinic in the city of Imperatriz-MA. This is a prospective, quantitative, cross-sectional study, which used data from the medical records of 70 patients with a previous diagnosis of BPH in a urology clinic in the city of Imperatriz-MA. There was a higher prevalence of LUTS in patients over 70 years of age, black, with complete elementary school, hypertensive, who had a high mean PSA level and high prostate volume. The identification of this profile is necessary to understand the conditions that may compromise the quality of life of patients with LUTS, suggesting the need for preventive and therapeutic measures that take into account the profile of the population treated at the urology clinic.